An Analysis of Maxim of Politeness Principle in Joe Rogan Experience Podcast - Harianja, May Lisabeth; Napitupulu, Fenty Debora; Sinaga, Nenni Triana (ALACRITY : Journal of Education, 2024)
This study aims to find out the type of maxim and the most dominant maxim of politeness principle in the Joe Rogan Experience Podcast. This study was compiled using a qualitative descriptive research method. The data of the study is the maxim of politeness principle in the transcript of the podcast Miley Cyrus and Joe Rogan. The author  ’s data source is from the “Youtube” Joe Rogan Experience Podcast. The number of data in this research is 60 data. The instrument of collecting data in this research was supported by observing the trancript of Joe Rogan Experience and Miley Cyrus to analyze the maxim of politeness principle and documentation from the video on Youtube from the Joe Rogan Experience Podcast. From the research that has been done, it was found that there is a difference in percentage between the 6 types maxim of politeness Principle. Tact maxim data with a percentage of 28,33%, Approbation maxim data with a percentage of 8,33%, Generosity Maxim data with a percentage of 8,33%, Modesty Maxim data with a percentage of 18,33%, Sympathy Maxim data with a percentage of 1,7%, Agreement Maxim data with a percentage 35%. So, it can be concluded that the results showed that Agreement Maxim is the most dominant type maxim of politeness principle in the podcast of “Joe Rogan Experience". Agreement Maxim is minimize disagreement between self and other, maximize agreement between self and other.